Transport Modelling of Citizens Evacuation - Šustr, Martin; Soušek, Radovan; Koloničný, Alois; Němec, Vladimír (City Net Scientific Research Center, 2016)
There is presented a software product intended for evacuations by using road transport while keeping to all the binding conditions. This software displays all the points important for evacuation and its process by means of digital maps, puts out routes in dependence on extraordinary event. It is possible to manually control inputs, parameters and process of the solution.
Modelování evakuace osob z postižených oblastí
Keywords: evacuations; software; road transport; Evakuace; softwarový produkt; silniční doprava